Perancangan dan Pengujian Sistem Pendingin untuk Pengolahan Cokelat Pasca-Tempering - Suhanto, Rhesti Nurlina; Fatwasauri, Icha; Dharmawan Hadi, Bagus; Septyansyah (Malikussaleh Journal of Mechanical Science and Technology, 2025)
The post-tempering cooling process in chocolate production is critical for achieving the desired quality attributes, including gloss, texture, and the stability of cocoa butter crystals. An essential aspect of the food processing industry is the demand for reliable cooling systems to maintain product quality, particularly in chocolate processing. This research focuses on designing and evaluating a cooling system based on an air cooled mini chiller integrated with an Air Handling Unit (AHU). The system gradually lowers the temperature of chocolate from 50°C to 27°C. The process involves creating a system based on cooling load calculations and thermal efficiency analysis, assembling it with a thermally insulated cabin, and conducting experimental testing to evaluate its performance. The testing environment was maintained at 31°C with relative humidity between 70% and 80%, without the use of a dehumidification system. The result indicates that the system can reduce the product temperature to 27°C in 38 minutes, with an efficiency of 63%. This represents an improvement compared to initial design efficiency, which was only 52%. Moreover, the cooling system operates effectively and stably, making it suitable for application in small-scale chocolate processing industries with a production capacity of 1–5 kg per cycle. This innovative solution is effective, stable, energy-efficient, and tailored for small scale chocolate production, and also offers future advancements in automated cooling technologies.